Mosque based sustainable financing model for micro enterprises using cash Waqf in Selangor state of Malaysia (IIUC Business Review, 2022)
Micro enterprises are emerging as an important sector in the economic system of Malaysia by contributing significantly to Gross Domestic Product (GDP) and providing employment opportunities to millions of workers in the country. Despite its importance in contributing towards the enhancement of the well-being of society and the continuous efforts from the government, micro-enterprises in Malaysia, are struggling with several issues. The majority of them are facing difficulties in obtaining financing for high risk. Hence, they face issues in obtaining financing from financial institutions which seek collateral and charge interest or fixed profit rate. Hence, this study proposes a mosque-based sustainable model for financing micro-enterprises using cash waqf with a significant feature of involving mosque-based administration committees (AJK) to intermediate between the Waqf Corporation of Selangor (PWS) (Waqf assets managing body of State Islamic Religious Council of Selangor (MAIS)) as Mutawalli of waqf and micro enterprises at village level. This study proposed a model for the Selangor state as the case study that may help address the financing constraints of micro-enterprises and further improve the well-being of Muslim society by better usage of cash waqf.IIUC Business Review Vol. 7-8, Dec. 2018-19 pp. 9-30